Architectural organization of facades according to principle of variability: videoecological aspect - Kozlova, Nataliia (Journal of Architecture and Urbanism, 2018)
This original conference topic is devoted to one of the actual problems concerning the current state of facades on apartment buildings – videoecology. Often the terrain dictates its conditions for the creation of banal solutions of facade forms; therefore, this paper focuses on what should be the new facade design that makes a person integrate into the new environment, become interested in this environment. The main purpose of this paper is to determine the method of forming a facade on the principle of variability, which involves in the architectural organization of the residential building facade functional and constructive variability with architectural and spatial solutions of this building. Research proposals in the paper are considered on the example of a competition project of a residential building in the historical centre of Subotica city, Serbia.